Cognitive training with and without additional physical activity in healthy older adults: cognitive effects, neurobiological mechanisms, and prediction of training success - Rahe, Julia; Becker, Jutta; Fink, Gereon R.; Kessler, Josef; Kukolja, Juraj; Rahn, Andreas; Rosen, Jan B.; Szabados, Florian; Wirth, Brunhilde; Kalbe, Elke (Frontiers in Aging Neuroscience, 2015)
Data is inconsistent concerning the question whether cognitive-physical training (CPT) yields stronger cognitive gains than cognitive training (CT). Effects of additional counseling, neurobiological mechanisms, and predictors have scarcely been studied. Healthy older adults were trained with CT (n=20), CPT (n=25), or CPT with counseling (CPT+C; n=23). Cognition, physical fitness, BDNF, IGF-1, and VEGF were assessed at pre- and posttest. No interaction effects were found except for one effect showing that CPT+C led to stronger gains in verbal fluency than CPT (p = .03). However, this superiority could not be assigned to additional physical training gains. Low baseline cognitive performance and BDNF, not carrying apoE4, gains in physical fitness and the moderation of gains in physical fitness x gains in BDNF predicted training success. Although all types of interventions seem successful to enhance cognition, our data do not support the hypotheses that CPT shows superior cognitive training gains compared to CT or that CPT+C adds merit to CPT. However, as CPT leads to additional gains in physical fitness which in turn is known to have positive impact on cognition in the long-term, CPT seems more beneficial. Training success can partly be predicted by neuropsychological, neurobiological, and genetic parameters. http://www.who.int/ictrp; ID: DRKS00005194